Research on AC Arc Fault Characteristics Based on the Difference between Adjacent Current Cycle - Gao, Yang; Wang, Li; Zhang, Yaojia; Yin, Zhendong (2019 Prognostics and System Health Management Conference (PHM-Qingdao), 2019)
Arc fault occurs frequently in aircraft system. Once the arc fault occurs, great harm will be caused, so it is necessary to diagnose and eliminate it in time. The physical phenomena of AC(Alternating Current) arc such as light and sound are not obvious when it occurs, because of its zero break characteristic. so it is difficult to detect. Therefore, it is necessary to study AC arc detection. In AC rectifier bridge load circuit, the current waveform under normal condition is similar to the waveform under arc condition, which makes it an aporia to detect AC arc. However, arc characteristics at present such as current change rate, flat shoulder ratio and harmonic component extracted from arc current are not suitable for arc fault diagnosis of rectifier bridge load circuit. Based on the automatic AC arc research platform, the serial and parallel arc faults experiments of the rectifier bridge load circuit are done. The condition of the experiment is 115V/360Hz-800Hz. The randomness of arc is amplified by the difference between adjacent current cycle's. On this basis, the effective value standard deviation of adjacent cycle's difference, the DC(Direct Current) component standard deviation of adjacent cycle's difference and the even harmonic power of adjacent cycle's difference are extracted from time domain and frequency domain respectively as AC arc fault characteristics. By the method of ratio and threshold, this paper verifies that the extracted characteristics are suitable for AC arc fault detection in rectifier bridge load circuits.